2022
DOI: 10.1590/fst.85622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of catalpa seed oil and pomegranate seed oil on body weight and intestinal flora in mice

Abstract: This study investigated the effects of different concentrations of catalpa seed oil (CSO) and pomegranate seed oil (PSO) on body weight and intestinal flora in mice. The results showed that the addition of 10% w/t CSO or PSO had a more significant effect than control (soybean oil) on reducing the body mass index of mice, which was reduced by 24.94% ± 0.08% (p < 0.01) and 25.88% ± 0.11% (p < 0.01), respectively. Histological observations indicated that no significant changes in the development and structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This protein lowers UA levels and protects the kidney. Wang et al (2022) established an HUA rat model using adenine and PO to evaluate the anti-HUA efficacy of poria powder. They found that poria powder significantly improved renal function, glomerular atrophy, and renal tubule dilation in HUA rats.…”
Section: Treatment Of Hua With Tcmmentioning
confidence: 99%
“…This protein lowers UA levels and protects the kidney. Wang et al (2022) established an HUA rat model using adenine and PO to evaluate the anti-HUA efficacy of poria powder. They found that poria powder significantly improved renal function, glomerular atrophy, and renal tubule dilation in HUA rats.…”
Section: Treatment Of Hua With Tcmmentioning
confidence: 99%
“…The mixture of hemp seed oil and water could induce changes in the intestinal flora of mice, increase the proportion of Bacteroidetes and decrease the proportion of Firmicutes, and improve the biodiversity of intestinal bacterial community in mice [24] . The research findings have also demonstrated that hemp seed oil can increase the levels of acetic acid and butyric acid and relieve constipation [25] .…”
Section: Modulation Of the Gut Microbiotamentioning
confidence: 99%
“…Functional oil plays a vital role in the human diet due to its abundant bioactive substances [ 1 ]. Dietary fat is an important part of the human diet, and its nutritional value is largely determined by its fatty acid composition, which is closely related to human health [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imbalances in the structure of the intestinal microbiota can have an impact on the host's metabolic and circulatory systems, with fatty acids playing a significant role as part of gut metabolites [ 21 ]. For example, imbalances in the intestinal microbiota have been associated with inflammatory bowel disease, colorectal cancer, obesity, diabetes, atherosclerosis, and liver disease [ 1 , 21 24 ]. It is widely recognized that diet plays a major role in influencing the composition and function of the human intestinal microbiota which regulates various immune functions within the body.…”
Section: Introductionmentioning
confidence: 99%